Evaluation of development levels of the provinces with grey cluster analysis based on human development index - Karakoç, Ömer (My University, 2019)
ÖZETİNSANİ GELİŞME ENDEKSİ ESAS ALINARAK GRİ KÜMELE ANALİZİ İLE İLLERİN GELİŞMİŞLİK SEVİYELERİNİN DEĞERLENDİRİLMESİBir ülkedeki kalkınma seviyesini belirlemek için yalnızca ekonomik göstergeler yeterli değildir. Yüksek düzeyde refah düzeyine sahip birçok ülkede, sosyal kısıtlamaları çözmedeki başarısızlık, bu ülke göstergelerinin geliştirilmesinin belirtilmesi için gerekli olduğunu göstermiştir. Ülkelerin gelişmişlik düzeyini belirlemek için çeşitli küresel endeksler kullanılmaktadır. Birleşmiş Milletler Kalkınma tarafından yayınlanan endekslerden biri İnsani Gelişme Endeksidir (İGE). Bu endeks geliri, eğitimi ve sağlık göstergelerini dikkate alarak gelişimi ölçmek için kullanılır. Bu çalışmada, Türkiye'deki iller İGE endeksini kullanarak gelişim düzeylerine göre gruplandırılmıştır. Bu bağlamda, benzer illeri gruplamak için gri bir kümeleme analizi kullanılmıştır. TUİK’ten alınan 81 ilin araştırma verileri, illere göre farklı seviyelere göre işaretlenmiş ve gelişim düzeyine göre üç kümeye ayrılmıştır. Ayrıca, illerin yaşam memnuniyeti ile elde edilen gri kümeler arasında bir korelasyon olup olmadığı analiz edilmiştir. Yaşam memnuniyeti ile eğitim sağlık ve gayri safi yurtiçi hasıla indikatörlerini içine alan insani gelişme indeksi arasında bağlantı olmadığı sonucuna varılmıştır. Çalışmanın sonuçları, refah artırma, iller arasındaki gelişme farklılıklarını azaltma, böylece az gelişmiş illerdeki nüfus yaşam düzeyi refahı ve koşullarının iyileştirilmesi amacıyla plan ve politikaların belirlenmesinde kullanılabilir.

ABSTRACTEVALUATION OF DEVELOPMENT LEVELS OF THE PROVINCES WITH GREY CLUSTER ANALYSIS BASED ON HUMAN DEVELOPMENT INDEXEconomic indicators alone are insufficient to determine development level of a country. In many high welfare level countries, failure to resolve social constraints has shown that indicators are needed to show development level of a country. For this purpose, various global indices are used to determine development level of the countries. One of the indices published by the United Nations Development Program is the Human Development Index (HDI). This index is used to measure development level by considering income, education and health indicators. In this study, provinces in Turkey were grouped according to their level of development using HDI index. In this context, a grey clustering analysis is applied to group similar provinces. TUIK research data for 81 provinces are divided into three clusters based on development level ranging between strong and weak and marked by the different colors on the map of Turkey. In addition, existence of correlation between life satisfaction of provinces and obtained grey clusters is analyzed. It is concluded that there is no similarity between life satisfaction and education, health and per capita money indicators in human development index. Study results can be used for making plans and policies to increase welfare, reduce development differences between provinces, and increase welfare of the population and conditions in underdeveloped provinces.
Keywords: Endüstri mühendisliği; Gri Kümeleme grey clustering; Industrial engineering